(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 2011)
Prestige is a valued capital for academic institutions. Although it is difficult to measure it or even to establish its components, there are no doubts that a talented corpus of students is one of the assets of higher education institutions. For students’ admission in Chilean universities, a national grading system is used and therefore, universities compete in capturing the best students. In addition, there are state financed subsidies associated to this attribute. The use of this financial transfer indicator as a mean to measure this portion of academic “wealth” of the institutions is proposed. By using the well known Gini index, its distribution is analyzed. For the sake of comparison, we also propose the use of another “wealth” indicator based on the official results of a national accreditation process. The results show a clearly biased system measured by the two before mentioned parameters with no significant correlation within them. Possible causes for this behavior are discussed.